2018
DOI: 10.3390/jcm7090292
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Progressive Resistance Training on Post-Surgery Incontinence in Men with Prostate Cancer

Abstract: We evaluated the efficacy of progressive resistance training of the pelvic floor muscle for post-prostatectomy incontinence. In this prospective study, 59 patients who underwent radical prostatectomy were evaluated preoperatively. Continence was sequentially assessed within 2 weeks postoperatively, and an exercise regimen was initiated at 6- and 12-weeks. The primary outcome was continent status and the secondary outcome was changes in muscle strength and endurance after the exercise intervention. Continence w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…Park et al [17], in his prospective study in two groups to evaluate the effectiveness of resistance training for postprostatectomy urinary incontinence, observed that the strength and resistance changes of the hip muscles were significantly greater in the continent group of the lower limbs. than in the incontinent group, revealing that the change in strength and resistance of these muscles may be related to obtaining urinary continence.…”
Section: Discussionmentioning
confidence: 99%
“…Park et al [17], in his prospective study in two groups to evaluate the effectiveness of resistance training for postprostatectomy urinary incontinence, observed that the strength and resistance changes of the hip muscles were significantly greater in the continent group of the lower limbs. than in the incontinent group, revealing that the change in strength and resistance of these muscles may be related to obtaining urinary continence.…”
Section: Discussionmentioning
confidence: 99%
“…Resistance band pelvic floor muscle exercise precisely induces contraction of the muscle group of the pelvic floor, taking advantage of the strength applied by the abductor of the hip joint plus the rectus. Park et al, 2018 and Hung et al (2011) indicated in their study that as long as patients receive guidance from health-care professionals on how to perform pelvic floor muscle exercises, there is no significant difference in the benefits from exercise performed at home and at the hospital. Prostate cancer tends to occur among men ages 65 years and above.…”
Section: Discussionmentioning
confidence: 99%
“…Research has shown that pelvic floor muscle exercises (Kegel exercises) can improve urinary incontinence and erectile dysfunction after prostatectomy (Fernández et al, 2015;Goonewardene, Gillatt, & Persad, 2018;Sayılan & Özbaş's, 2018) and are a high priority for nonsurgical treatment (Yani et al, 2018). Furthermore, Park et al (2018) observed that a change in hip extensor muscle strength was the only significant parameter predicting achievement of continence. Hung, Hsiao, Chih, Lin, and Tsauo (2011) emphasized that pelvic floor muscle contraction exercises should begin as soon as possible after surgery.…”
mentioning
confidence: 99%
“…The study demonstrated that several approaches and samples showed promising results in minimizing postoperative urinary incontinence, mainly accelerating recovery and healing or decreasing symptoms. Park et al [38] found that the strength and resistance changes of the hip muscles were significantly greater in the continent group of the lower limbs than in the incontinent group in their prospective study in two groups to evaluate the effectiveness of resistance training for post prostatectomy urinary incontinence.…”
Section: Discussionmentioning
confidence: 99%